Working in Venezuela: How the Crisis has Affected the Labor Conditions - Yohama Caraballo-Arias; Jesús Madrid; Marcial Barrios (Ubiquity Press, 2018)
Background: Venezuela, the country with the largest oil reserves in the world, is facing the worst economic, social and political crisis in its history; which has notably affected the quality of life of the workforce and the entire population. Objectives: Identify and analyze the main social factors derived from the Venezuelan crisis, which are affecting the workers' health and working conditions. Methods: Document study. Several sources of information from the last twenty years were consulted, ranging from public statistics and reports, newspaper articles, and results of scientific research. The information gathered was carefully studied to ensure that only reliable sources were used to ultimately reach valid conclusions. Results: Both workers from the formal and informal sector and their families are struggling to fulfill their basic needs. Low salaries and soaring inflation have resulted in a dramatic reduction in the purchasing power of the people. General violence and high prices of basic goods are some of the major problems affecting workers both inside and outside of their working environment. Being a formal employee is no longer a guarantee for an acceptable quality of life. As a result, over 1.6 million Venezuelans have left their country since 2015 in a migration crisis never seen before in Latin America. Conclusion: Quality of life and wellbeing of most of the Venezuelan population has being deteriorated in the last 5 years and Occupational Safety and Health (OSH) is not a priority for enterprises in the middle of the economic emergency and general deterioration of daily life. Despite the relevance of this problem, research on the subject is very limited. Recent and pertinent data is needed to properly identify and measure the risks and negative consequences that workers and families are exposed caused by the ongoing crisis.